2018
DOI: 10.1523/jneurosci.1409-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Synaptotoxicity in Alzheimer's Disease Involved a Dysregulation of Actin Cytoskeleton Dynamics through Cofilin 1 Phosphorylation

Abstract: Amyloid-␤ (A␤) drives the synaptic impairment and dendritic spine loss characteristic of Alzheimer's disease (AD), but how A␤ affects the actin cytoskeleton remains unknown and contentious. The actin-binding protein, cofilin-1 (cof1), is a major regulator of actin dynamics in dendritic spines, and is subject to phospho-regulation by multiple pathways, including the Rho-associated protein kinase (ROCK) pathway. While cof1 is implicated as a driver of the synaptotoxicity characteristic of the early phases of AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 50 publications
5
77
0
Order By: Relevance
“…In APP/PS1 mice (a mouse model of AD) an increased cofilin activation/dephosphorylation was observed [183,184]. The analysis of the PSD-enriched fraction of both APP/PS1 mice and AD brains revealed a significant increase in cofilin phosphorylation/inactivation in the postsynaptic compartment [185]. Another study showed that cofilin phosphorylation state depends on the stage of the pathology, since an increased activation (dephosphorylation) is detected in APP/PS1 mice brains at four months of age while cofilin is strongly phosphorylated (inactivated) at 10 months of age, corresponding to a full-blown pathology stage [181].…”
Section: Actin Cytoskeleton Pathology In Admentioning
confidence: 99%
“…In APP/PS1 mice (a mouse model of AD) an increased cofilin activation/dephosphorylation was observed [183,184]. The analysis of the PSD-enriched fraction of both APP/PS1 mice and AD brains revealed a significant increase in cofilin phosphorylation/inactivation in the postsynaptic compartment [185]. Another study showed that cofilin phosphorylation state depends on the stage of the pathology, since an increased activation (dephosphorylation) is detected in APP/PS1 mice brains at four months of age while cofilin is strongly phosphorylated (inactivated) at 10 months of age, corresponding to a full-blown pathology stage [181].…”
Section: Actin Cytoskeleton Pathology In Admentioning
confidence: 99%
“…Despite the strong evidence for a role of cofilin activation and oxidation in AD pathogenesis, other studies have shown that cofilin inactivation may also play a role in AD pathogenesis. In the postsynaptic density (PSD) fraction of AD and APP/PS1 mouse brains, phospho-cofilin is increased, and short duration (30 min) A␤ 1-42 oligomer treatment promotes cofilin phosphorylation together with F-actin stabilization in dendritic spines [116], which decreases synaptic plasticity. Another study showed that A␤ oligomers increase cofilin phosphorylation and actin polymerization selectively in basal forebrain cholinergic neurons but not in non-cholinergic neurons via a p75-dependent mechanism [117].…”
Section: De Kang and Ja Woo / Cofilin In Ad Pathogenesismentioning
confidence: 99%
“…Furthermore, ROCK1 and ROCK2 protein abundances are increased among mild cognitive impairment (MCI) and AD patients, implying that ROCKs may contribute to synaptic loss in early disease stages (17,26). Pharmacologic studies with Fasudil and Y-27632, the most widely characterized pan-ROCK inhibitors, suggest beneficial effects of ROCK inhibitors in AD models (27,28). However, these and other ROCK inhibitors are not isoform-specific and can inhibit other AGC family kinases, including protein kinase A (PKA) and protein kinase C (PKC) (29).…”
Section: Introductionmentioning
confidence: 99%